Implementasi Permainan Tradisional Berbasis Metode Sokratik Dalam Mengembangkan Character Strength Wisdom Siswa Sekolah Dasar - Desi Nur Rachmawati, - (2022)
The traditional game based on the socratic method in developing the character strength wisdom of fourth graders at SD Negeri Cibogo. The purpose of this study was to determine the effect of the traditional engklek game based on the socratic method on the character strength wisdom of elementary school students. This study uses a quantitative method of Pre-experimental Design with one group pre-test posttest. The sample of this study consisted of 25 fourth grade students of SD Negeri Cibogo. In the implementation of learning, students follow the traditional engklek game using the socratic method which was carried out during the research. The research data was collected using a research instrument in the form of a questionnaire (questionnaire) to measure the influence of the socratic-based traditional engklek game in developing the character strength of students' wisdom. The results showed that there was an influence of the traditional engklek game using the socratic method in the character strength of students' wisdom. This research has implications for creativity, curiosity, open-mindedness, love and perspective of fourth graders at SD Negeri Cibogo in the traditional engklek game. Keywords: Traditional Game, Socratic Method, Character Strength Wisdom